Reseña de libro (2011)
ABSTRACT: For over thirty years Don DeLillo has been one of a select group of American novelists that have assumed the task of examining America’s relationship with itself and with the world at large. He has received the National Book Award and the PEN Faulkner award among many others. In this his fourteenth novel, he writes about the events of September 11, 2001 and its effects on half a dozen New Yorkers. The novel Falling Man was published six years after the attacks and joins at least ten others that have come to create the 9/11 subgenre of fiction.